Pengaruh Urutan Proses Osmotik-Termal dan Teknik Pengeringan terhadap Mutu Sensoris Manisan Herbal Jahe - Cahyaning Rini Utami; Roisatul Ainiyah; Senja Ike Rismawati (Yayasan Literasi Sains Indonesia, 2026)
This study evaluated how the sequence of osmotic–thermal processing and the drying method influence the sensory quality of candied ginger slices. We designed four processing treatments (P1–P4) that differed in the order of sugar contact and heating, as well as the end-step method (drying or sugar crystallization). Twenty panelists rated color, aroma, taste, texture, and overall liking on a 1–5 hedonic scale. We assessed differences among treatments using the Friedman test (α = 0.05). We selected the best treatment using a modified De Garmo effectiveness index with weighted sensory parameters. The results showed significant treatment effects across all main sensory attributes. P4 consistently achieved the highest acceptance scores and demonstrated a more favorable profile in derived attributes noted by panelists, including a more uniform appearance, a more pleasant aroma, a better-balanced taste, and a more acceptable bite. Consequently, P4 produced the highest total effectiveness score in the De Garmo selection. These findings indicate that optimizing the osmotic thermal sequence particularly when finalized through controlled crystallization can enhance consumer acceptance and support more consistent product quality for small-scale to semi-commercial production.